2018
DOI: 10.3390/ht7040038
|View full text |Cite
|
Sign up to set email alerts
|

The Prenatal Microbiome: A New Player for Human Health

Abstract: The last few years have featured an increasing interest in the study of the human microbiome and its correlations with health status. Indeed, technological advances have allowed the study of microbial communities to reach a previously unthinkable sensitivity, showing the presence of microbes also in environments usually considered as sterile. In this scenario, microbial communities have been described in the amniotic fluid, the umbilical blood cord, and the placenta, denying a dogma of reproductive medicine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 80 publications
(171 reference statements)
1
52
0
13
Order By: Relevance
“…Until recently, the foetus has been considered to exist in a sterile environment with initial microbial colonization of the newborn taking place during birth (51). Recent studies have reported the detection of microbes from amniotic fluid, placenta and meconium, suggesting that microbial colonization may begin in utero (52, 53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the foetus has been considered to exist in a sterile environment with initial microbial colonization of the newborn taking place during birth (51). Recent studies have reported the detection of microbes from amniotic fluid, placenta and meconium, suggesting that microbial colonization may begin in utero (52, 53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of studies have reported bacterial communities from meconium specimens (54). Dysbiosis of faecal bacterial profiles early in life has been associated with a number of neonatal diseases, including asthma, allergic diseases, and obesity (51), which further emphasises the importance of in utero colonization on the health of newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Our gut, food, and microbiome are also connected with our nervous system. Humans might get their prenatal microbiome (Aagaard et al, 2014;Parnell et al, 2017;D'Argenio, 2018) or at least be exposed to some bacteria (de Goffau et al, 2019) while in the uterus, and it is suggested that the gut-brain-bidirectional axis originates in utero (Borre et al, 2014;Jasarevic et al, 2017;Martin et al, 2018). Our gut and brain communicate via neurobiochemical, neuroendocrinal, and neuroimmune mechanisms, which are still unclear, and can be the result of different stages of development.…”
Section: Diet and Its Effect On Gut Microbiome Composition And Functionmentioning
confidence: 99%
“…Several findings using both culture and metagenomic techniques have suggested the presence of a low biomass microbial community in the healthy placenta [39][40][41][42][43]. The abundance of different species of Lactobacillus, Propionibacterium, and members of the Enterobacteriaceae family have been detected by DNA-based studies in placental tissue of pregnant women at term and it is under debate [16].…”
Section: Placental Microbiota and Fetal Colonizationmentioning
confidence: 99%